ANALISIS TINGKAT PENDAPATAN USAHA TERNAK AYAM RAS PEDAGING SISTEM KEMITRAAN DAN NON KEMITRAAN - Titin Agustina (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2007)
Poultry commodity has good market prospect because supported by the characteristics of poultry product that can be gotten by Indonesian that mostly moslem, the cost is cheap with easy access because it’s a public goods. The poultry industry faces various problems continually, they are; broiler price fluctuation, day old chick price fluctuation, the increase of weft price and Avian Influenza issue. Many constraints force breeder to be wise in taking decisions on broiler industry. One of them is decision of working system that will be held in order to maximalize breeder income. This research held in Gumukmas, Jember where broiler industry is done through two system they are partnership and non partnership system. This research held with sampling method and the results show non partnership system give more profit but give lower income contribution to family than partnership system. Key Words : Broiler, Partnership, Non Partnership